Enhancing performance and emission on a turbocharged gasoline engine - -, -
The turbocharger became a trend in the automotive cars engine manufacturing developments. Nowadays turbocharger are used to develop and improver the engine performance and, it now applied to produce a high performance and improve fuel economy for a vehicles with small and medium engine size. This development lead the car manufactures to use a mid-sized engine rang with a turbocharger system. The main objectives of this project is to design and analysis a turbocharger turbine performance and the effect of number of blades on the turbine performance based on the GT2056 turbocharger model, which is a capable application for engine displacement of 1.4 to 2.0L. The study explain the designing and analysis of the turbocharger turbine, CAD and CFturbo are used to design the turbocharger turbine and housing and the analysis of the turbocharger turbine performance is done by using the numerical simulation software ANSYS 18.0 and TCFD 18.02. In this study an attempt to investigate the turbocharger turbine performance characteristics for various rotational speeds, mass flowrate and temperature and build a turbine performance map and investigate the effect of the number of blades on the turbocharger performance then identify the most suitable number of blades for the turbocharger turbine. However, the turbocharger turbine performance are analysed and reported.